Design of an e-encyclopedia of the order of odonata from sumatra as student teaching material - Siregar, Nurul Safitri; Dimenta, Rivo Hasper; Sari, Novi Fitriandika (JPBIO (Jurnal Pendidikan Biologi), 2024)
This research discusses the design of the E-Encyclopedia of the Order of Odonata as teaching material for junior high school students. This research aims to introduce how to design an E-encyclopedia of the Order of Odonata from Sumatra which can be used as teaching material for junior high school students, especially children aged (13-15 years) in the Sumatra region. The urgency is that junior high school children become familiar with the various types of the Odonata Order from Sumatra so that the identity of the Odonata Order is maintained and maintained. This research is design research consisting of three phases, namely Preliminary research, Prototyping phase, and assessment phase. The design of the E-Encyclopedia of the Odonata Order from Sumatra is an effort to develop media in studying various types of the Odonata Order from Sumatra whose development is viewed from language, material, and media. Through the development activities carried out, an E-Encyclopedia Product of the Order of Odonata from Sumatra was obtained as suitable teaching material.